Economic interactions between climate change and outdoor air pollution - Lanzi, Elisa (OECD Publishing, 2019)
Climate change and outdoor air pollution are two of the most challenging environmental issues that modern society faces. These challenges are strongly linked through their emission sources, the sectors they affect and the policies that can be implemented to reduce emissions. They also interact in the way they affect economic growth in the coming decades, although this aspect has been neglected in the literature. This paper presents the first global analysis of the joint economic consequences of climate change and outdoor air pollution to 2060, in the absence of new policies to address these challenges. A common methodology and a consistent modelling framework is used to specify the main economic interaction effects. While this paper provides a useful framework to analyse the interactions between two environmental issues in the economic system, the results need to be interpreted carefully, because of limited data availability
Keywords: Environment